2013
DOI: 10.1038/nbt.2647
|View full text |Cite
|
Sign up to set email alerts
|

DNA targeting specificity of RNA-guided Cas9 nucleases

Abstract: The Streptococcus pyogenes Cas9 (SpCas9) nuclease can be efficiently targeted to genomic loci by means of singleguide RNAs (sgRNAs) to enable genome editing1–10. Here, we characterize SpCas9 targeting specificity in human cells to inform the selection of target sites and avoid off-target effects. Our study evaluates >700 guide RNA variants and SpCas9-induced indel mutation levels at >100 predicted genomic off-target loci in 293T and 293FT cells. We find that SpCas9 tolerates mismatches between guide RNA and ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

125
4,302
12
25

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 4,155 publications
(4,464 citation statements)
references
References 28 publications
125
4,302
12
25
Order By: Relevance
“…Cas9-Venus C-terminal fusion protein (Cas9-CV) showed similar sgRNA-dependent in vivo cleavage activity on its genomic target as untagged wild type protein, while N-terminal Venus-Cas9 (NV-Cas9) fusion showed no activity (Supplementary information, Figure S1A). In addition, Cas9-CV also showed similar cleavage activity on a previously identified emx1 off-target (emx1-OT4) [9,11] but did not cleave the control locus (Supplementary information, Figure S1B-S1D). Mutations of both HNH nuclease and RuvC catalytic domains (DM-Cas9-CV) abolished the cleavage activity (Supplementary information, Figure S1A, lane5).…”
mentioning
confidence: 61%
“…Cas9-Venus C-terminal fusion protein (Cas9-CV) showed similar sgRNA-dependent in vivo cleavage activity on its genomic target as untagged wild type protein, while N-terminal Venus-Cas9 (NV-Cas9) fusion showed no activity (Supplementary information, Figure S1A). In addition, Cas9-CV also showed similar cleavage activity on a previously identified emx1 off-target (emx1-OT4) [9,11] but did not cleave the control locus (Supplementary information, Figure S1B-S1D). Mutations of both HNH nuclease and RuvC catalytic domains (DM-Cas9-CV) abolished the cleavage activity (Supplementary information, Figure S1A, lane5).…”
mentioning
confidence: 61%
“…Earlier works have studied the specificity of the gRNA design. Although Cong et al reported highly specific gRNA targeting and abolished gRNA function, caused by mismatches at the last 11 bases on the 20‐mer‐targeting region,2 subsequent work indicated that any mismatches on the 20‐mer‐targeting region of gRNA might cause Cas9 off‐targeting 29. With the optimized micelle, no significant editing was observed in the off‐targeting sites identified by both Cas‐OFFinder and BLAST (off/on ratio ≈0; Figure 3F,G).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the overall targeting and HDR efficacy and mosaicism, one safety concern regarding clinical application of gene correction in human embryos is that CRISPR-Cas9 can induce undesirable off-target mutations at genome regions that are highly homologous to the targeted sequence [22][23][24] . Therefore, we conducted a comprehensive, whole-genome In the S-phase-injected group, each mosaic embryo (green) contained blastomeres with different genotypes.…”
Section: Off-target Consequences In Repaired Human Embryosmentioning
confidence: 99%